2021
DOI: 10.30543/10-1(2021)-7
|View full text |Cite
|
Sign up to set email alerts
|

Leadership and Decision-making Style among Women Entrepreneurs: A Case of Malaysia

Abstract: Women entrepreneur plays a catalytic role in economic development, as women constitute half of Malaysia's population. The contribution of women entrepreneurs in the country's economy is significant and may not ignore. Malaysia is a multicultural and multiethnic society comprised of Malays, Chinese, Indian and other local ethnics. The present study investigates the leadership and decision-making style among Malaysian women entrepreneurs. The present study adopted the qualitative research strategy, and ten women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Women's entrepreneurial activities in the SSA region have not only had an impact on reducing unemployment but have also brought about various social benefits. For instance, these activities have contributed to reducing child trafficking and prostitution in Nigeria (Ogundana et al, 2018), improving child education rates in Ghana and the Republic of Niger (Chea, 2008;Otoo et al, 2012), increasing family nutritional rates by 33% in Botswana (Ama et al, 2014), reducing crime levels by 23.3% in Ogun State, Nigeria (Iyiola and Azuh, 2014;, and playing a crucial role in alleviating hunger and poverty in Kenya (IFC, 2014;Misango and Ongiti, 2013). These examples demonstrate the transformative potential of women-owned SMEs within African societies, positively impacting various dimensions of social development.…”
Section: Women's Entrepreneurship In Sub-saharan Africamentioning
confidence: 99%
“…Women's entrepreneurial activities in the SSA region have not only had an impact on reducing unemployment but have also brought about various social benefits. For instance, these activities have contributed to reducing child trafficking and prostitution in Nigeria (Ogundana et al, 2018), improving child education rates in Ghana and the Republic of Niger (Chea, 2008;Otoo et al, 2012), increasing family nutritional rates by 33% in Botswana (Ama et al, 2014), reducing crime levels by 23.3% in Ogun State, Nigeria (Iyiola and Azuh, 2014;, and playing a crucial role in alleviating hunger and poverty in Kenya (IFC, 2014;Misango and Ongiti, 2013). These examples demonstrate the transformative potential of women-owned SMEs within African societies, positively impacting various dimensions of social development.…”
Section: Women's Entrepreneurship In Sub-saharan Africamentioning
confidence: 99%
“…In rural Kenya, women are involved in agriculture as farmers on their own account, as unremunerated workers on family lands, and as paid or unpaid laborers on other lands (Alila and Atieno, 2016;Diiro et al, 2018;Wanjala and Were, 2009). They are also involved in petty trade of agricultural produce to earn an income for their families' subsistence (Mehra and Rojas, 2008;Misango and Ongiti, 2013). Kenya has made progressive steps towards advancing women's rights to property and land, specifically through putting in place appropriate legislation (Kameri-Mbote and Muriungi, 2018;Landesa, 2014;Musangi, 2017).…”
Section: Contextualizing the Literature: From The Global To The Localmentioning
confidence: 99%
“…Management, on the other hand, is a traditional form of power and responsibility, which focuses on stability and predictability by creating goals, plans, resource allocations, resolving issues and problems and monitoring of overall result (Algahtani, 2014;Hodge et al, 2017). Past literature demonstrates numerous definitions on the term "leadership", but there continues to exist a lack of agreement among researchers on one standard definition as House (1971) defines leadership as "the ability of an individual to influence, motivate and enable others to contribute towards the effectiveness and success of the organisations of which they are members", whereas previous researches revealed that character traits such as intelligence, determination, integrity, charisma, sociability, adaptability and self-confidence are essential traits for one to be perceived as a leader (Bellon et al, 2017;Dwiri and Okatan, 2021;Isa et al, 2021). Furthermore, different leadership styles can also impact the organisations and staff.…”
Section: Literature Reviewmentioning
confidence: 99%